1970
DOI: 10.2323/jgam.16.1_15
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Different Sized Cells of Baker's Yeast

Abstract: Commercial baker's yeast cells were fractionated into small and large sized cells by repeated centrifugation, and characterization of the small cells was carried out by comparison with the original cells. The small cell preparation consists of more than 90% of small sized age 0 cells, whose length of major axis ranged from 2.5 to 4.5 ,ce. There was no significant difference in DNA content and nuclear appearance between the small and original cell preparations. Respiratory activities were also essentially the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

1973
1973
1981
1981

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…It was also confirmed that these cells are, without exception, age 0 cells which have not undergone any budding in the past (6).…”
supporting
confidence: 58%
See 4 more Smart Citations
“…It was also confirmed that these cells are, without exception, age 0 cells which have not undergone any budding in the past (6).…”
supporting
confidence: 58%
“…Because the cells entering or nearly entering into the stationary phase were employed at the beginning of the culture either in the synchronous culture or in the single-cell culture, definite time called lag period was required up to the 1st budding ; thereafter, however, the cells grew normally and did not require any lag period for the 2nd and 3rd budding of the mother cells (6,29,30).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations